Consumption of a high-salt diet by ewes during pregnancy alters nephrogenesis in 5-month-old offspring - Tay, S.; Blache, D.; Gregg, Keith; Revell, D. (Cambridge University Press, 2012)
Maternal nutrition during pregnancy can affect kidney development in the foetus, which may lead to adverse consequences in the mature kidney. It was expected that high-salt intake by pregnant ewes would lead to a reduction in foetal glomerular number but that the ovine kidney would adapt to maintain homoeostasis, in part by increasing the size of each glomerulus. Merino ewes that were fed either a control (1.5% NaCl) or high-salt (10.5% NaCl) diet during pregnancy, as well as their 5-month-old offspring, were subjected to a dietary salt challenge, and glomerular number and size and sodium excretion were measured. The high-salt offspring had 20% fewer glomeruli compared with the control offspring ( P,0.001), but they also had larger glomerular radii compared with the control offspring ( P,0.001). Consequently, the cross-sectional area of glomeruli was 18% larger in the high-salt offspring than in the control offspring ( P,0.05). There was no difference in the daily urinary sodium excretion between the two offspring groups ( P.0.05), although the high-salt offspring produced urine with a higher concentration of sodium. Our results demonstrated that maternal high-salt intake during pregnancy affected foetal nephrogenesis, altering glomerular number at birth. However, the ability to concentrate and excrete salt was not compromised, which indicates that the kidney was able to adapt to the reduction in the number of glomeruli.